Design of transceiver front end of subscriber radio terminal for fixed subscriber in rural areas ... [et al.] / [microfilm] - 299408 Jamaludin Samat; Johari Kasim; Sri Murni; Tan, Kim Geok; Tay, Yong Haur (Skudai : Universiti Teknologi Malaysia, 1996)
Thesis (Master of Electrical Enginering) - Universiti Teknologi Malaysia, 1996